Νεκρικό δαχτυλίδι από το Κιλκίς - Τσαντσάνογλου Κυριάκος (Tekmeria, 2020)
The bronze inscribed funerary ring published and discussed in this paper was discovered in Kilkis (ancient Crestonia). The lettering suggests a late fourth or early third-century BC date. The most important features of the ring are the inscribed Thessalian personal names: the name of the deceased woman is Λάρισα, named after the principal Pelasgiotid city. Her husband’s name is Ἀστόδημος or Ἀστόδαμος, i.e. the common Ἀριστόδαμος, in the Pelasgiotid dialect. Apart from the ring-inscription, there are more finds suggesting a Thessalian presence in North Mygdonia or South Crestonia during the aforementioned period. The inscription on the lip of the bronze crater’s mouth of the Derveni tomb B refers to its owner (or the deceased man) as coming from Larisa, in a strict Pelasgiotid dialect. The name Κλείτα, inscribed on a funerary ring found in the Derveni tomb Z, is a typical female name of Larisa. The owner of the Derveni papyrus, found in the remnants of the pyre of tomb A, twice changes the word μάγοι of the original text to ταγοί, as the Thessalian magistrates were named. An inscribed grave stele found in Mygdonia presents both linguistic and decorative features that suggest a connection with Pelasgiotid Thessaly. Finally, the paper suggests that an unattested population transplant from Pelasgiotis to Mygdonia was carried out by Philip II in the mid-fourth century BC, when he was proclaimed an archon of Thessaly.